Diagnostic value of bronchoalveolar lavage fluid galactomannan assay for invasive pulmonary aspergillosis in adults: A meta‐analysis. (2nd November 2022) - Li, Chang; Sun, Lin; Liu, Yin; Zhou, Hongbing; Chen, Jianguo; She, Min; Wang, Yong
Abstract: What is known and objective: To analyse the diagnostic accuracy of bronchoalveolar lavage fluid galactomannan (BALF‐GM) assay for invasive pulmonary aspergillosis (IPA) in adults to determine the optimal diagnostic cut‐off by meta‐analysis. Methods: PubMed, Embase, Web of Science, Cochrane Library, China national knowledge infrastructure (CNKI), and China Wanfang databases were searched to collect relevant studies on the diagnostic value of BALF‐GM for IPA from inception to March 2022. The summary receiver operating characteristic (SROC) curve was drawn to determine the optimal diagnostic cut‐off. Results and discussion: Nineteen articles (56 data sets) were included. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were 0.79 (95% CI: 0.72–0.84), 0.92 (95% CI: 0.88–0.94), 9.25 (95% CI: 6.84–12.52), 0.23 (95% CI: 0.18–0.30), 39.44 (95% CI: 29.55–52.65), and 0.92 (95% CI: 0.90–0.94), respectively. The area under the curves (AUCs) were 0.92, 0.86, 0.93, 0.89, 0.88, and 0.94 when the cut‐off values were 0.5, 0.8, 1.0, 1.5, 2.0, and 3.0, respectively. Sixteen studies were included in the combined analysis when the cut‐off value was 0.5. The results showed that the pooled sensitivity, specificity, PLR, NLR and DOR of BALF‐GM (cut‐off 0.5) for the diagnosis of IPA were 0.89 (95% CI: 0.83–0.93), 0.79 (95% CI: 0.71–0.86), 4.33 (95% CI: 3.04–6.16), 0.14 (95% CI: 0.09–0.22), and 31.51 (95% CI: 17.43–56.98). The AUC was 0.92 (95% CI: 0.89–0.94). What is new and conclusions: BALF‐GM has excellent diagnostic accuracy for adult IPA, which can be diagnosed early and treated early to reduce the mortality rate. Considering the sensitivity, specificity, PLR and NLR, the recommended diagnostic cut‐off of BALF‐GM for adult IPA is 0.5. Abstract : Databases including PubMed, Embase, Web of Science, Cochrane Library, China national knowledge infrastructure, and China Wanfang were searched to retrieve relevant studies on the diagnostic value of bronchoalveolar lavage fluid galactomannan (BALF‐GM) for invasive pulmonary aspergillosis (IPA) from inception to March 2022.The summary receiver operating characteristic curve was drawn to determine the optimal diagnostic cut‐off. Furthermore, we found that BALF‐GM had excellent diagnostic accuracy for adult IPA, which could be diagnosed early and treated early to reduce the mortality rate. Considering the sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio, the recommended diagnostic cut‐off of BALF‐GM for adult IPA is 0.5.